2019
DOI: 10.1111/jdv.15653
|View full text |Cite
|
Sign up to set email alerts
|

Safety of selective IL‐23p19 inhibitors for the treatment of psoriasis

Abstract: Psoriasis is a chronic disease that requires long‐term treatment. Consequently, understanding the safety and tolerability of any potential treatment over time is critical to effective prescribing. The biologic agents currently available for the treatment of psoriasis target a number of different inflammatory cytokines involved in psoriasis disease pathogenesis. The monoclonal antibodies tildrakizumab, guselkumab and risankizumab target the p19 subunit that is specific to interleukin (IL)‐23. This article revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 58 publications
1
53
0
3
Order By: Relevance
“…It was noted that the most common infection reported was an upper respiratory tract infection. Infections classified as serious demonstrated no significant difference between the groups [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that the most common infection reported was an upper respiratory tract infection. Infections classified as serious demonstrated no significant difference between the groups [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Safety results of tildrakizumab are similar to what has been reported from analyses of phase III trials regarding other IL-23p19 inhibitors. 43 Rates of AEs and SAEs are also mostly comparable across groups in phase III studies of guselkumab and risankizumab. 43 However, one systemic review and meta-analysis on IL-23p19 blockers indicated an increased incidence rate of infections when treating with guselkumab and risankizumab.…”
Section: Aes In Phase III Trialsmentioning
confidence: 95%
“…43 Rates of AEs and SAEs are also mostly comparable across groups in phase III studies of guselkumab and risankizumab. 43 However, one systemic review and meta-analysis on IL-23p19 blockers indicated an increased incidence rate of infections when treating with guselkumab and risankizumab. 44 The reported infections did not evolve to serious infections or other serious events.…”
Section: Aes In Phase III Trialsmentioning
confidence: 95%
See 1 more Smart Citation
“…[58][59][60] For the IL23/p19 inhibitors: guselkumab, risankizumab and tildrakizumab; the IL17 receptor blocker: brodalumab; the IL17 inhibitors: ixekizumab and secukinumab, no increased risk for TB reactivation has yet been reported. [61][62][63][64] We also note that TB testing is no longer mandatory from a scientific point of view (but is still present as a reimbursement criterion) for IL17 and IL23 antagonists, as well as with apremilast and acitretin. We note however that there are limited data available with the IL12/23 inhibitor: ustekinumab; the IL23/p19 inhibitors: guselkumab, risankizumab and tildrakizumab; the IL17 receptor blocker: brodalumab in these patients.…”
Section: Chronic Infectionsmentioning
confidence: 99%